Reducing bycatch through a risk pool: A case study of the U.S. West Coast groundfish fishery. (October 2018) - Kauer, Kate; Bellquist, Lyall; Gleason, Mary; Rubinstein, Aliya; Sullivan, Joe; Oberhoff, Dwayne; Damrosch, Lisa; Norvell, Michelle; Bell, Michael
Abstract: Voluntary collective agreements among fishermen can improve the environmental and economic performance of a fishery, particularly when local leadership, strong incentives, catch accountability, and operational support are in place. Rights-based fisheries, such as Individual Fishing Quota (IFQ) systems, incentivize fishermen to act collectively to reduce fishing impacts, enhance stock health, and improve economic outcomes. However, developing cooperatives requires durable contracts, operational capacity, funding, and the ability to track, monitor, and enforce agreed-upon catches and fishing practices. This project focuses on the U.S. West Coast groundfish trawl IFQ fishery, and how the formation of a voluntary collective agreement, in the form of a bycatch risk pool (California Groundfish Collective), achieved improved fishery performance and other ancillary benefits. Up-front investment in the risk pool by a conservation non-governmental organization (NGO) provided both capacity and quota to cover transaction costs and incentivize transition to a cooperative model that was implemented across 5 ports and more than 48, 000 km 2 of fishing grounds off California. The challenges encountered in developing and operating the risk pool offer insights into designing and implementing voluntary collective agreements. By using spatial fishing plans and technology for collecting and sharing catch information, risk pool members reduced bycatch of overfished species relative to the fleet at large. Risk pool members were also able to use their spatial fishing data to inform a seafood sustainability rating and propose areas for Essential Fish Habitat protection, their quota pounds to support collaborative research on overfished species, and their collective membership to advocate for policy.